Two new species of Polydrusus (Polydrusus) from Turkey, Iran and Greece (Coleoptera: Curculionidae: Entiminae: Polydrusini) - Borovec, Roman; Germann, Christoph (Zootaxa, 2013)
Polydrusus (Polydrusus) kadleci sp. n. from northeastern Turkey and western Iran and P. (Polydrusus) wymanni sp. n. from Samos Island (Greece) are described. Both species show characteristic raised setae on the pronotum and elytra, the length of which is apparently sexually dimorphic. The lectotype of P. (Polydrusus) mecedanus Reitter, 1908 is designated. New faunistic data of other species near P. (Polydrusus) reitteri Stierlin, 1884 are presented.